Identification of new adventitious rooting mutants amongst suppressors of the Arabidopsis thaliana superroot2 mutation - Pacurar, Daniel Ioan (Oxford University Press, 2014)
The plant hormone auxin plays a central role in adventitious rooting and is routinely used with many economically important, vegetatively propagated plant species to promote adventitious root initiation and development on cuttings. Nevertheless the molecular mechanisms through which it acts are only starting to emerge. The Arabidopsis superroot2-1 (sur2-1) mutant overproduces auxin and, as a consequence, develops excessive adventitious roots in the hypocotyl. In order to increase the knowledge of adventitious rooting and of auxin signalling pathways and crosstalk, this study performed a screen for suppressors of superroot2-1 phenotype. These suppressors provide a new resource for discovery of genetic players involved in auxin signalling pathways or at the crosstalk of auxin and other hormones or environmental signals. This study reports the identification and characterization of 26 sur2-1 suppressor mutants, several of which were identified as mutations in candidate genes involved in either auxin biosynthesis or signalling. In addition to confirming the role of auxin as a central regulator of adventitious rooting, superroot2 suppressors indicated possible crosstalk with ethylene signalling in this process.